Kinetic and structural characterization of the first B3 metallo-β-lactamase with an active-site glutamic acid - Wilson, LA; Knaven, EG; Morris, MT; Monteiro Pedroso, M; Schofield, CJ; Brück, TB; Boden, M; Waite, DW; Hugenholtz, P; Guddat, L; Schenk, G (American Society for Microbiology, 2021)
The structural diversity in metallo-β-lactamases (MBLs), especially in the vicinity of the active site, has been a major hurdle in the development of clinically effective inhibitors. Representatives from three variants of the B3 MBL subclass, containing either the canonical HHH/DHH active-site motif (present in the majority of MBLs in this subclass) or the QHH/DHH (B3-Q) or HRH/DQK (B3-RQK) variations, were reported previously. Here, we describe the structure and kinetic properties of the first example (SIE-1) of a fourth variant containing the EHH/DHH active-site motif (B3-E). SIE-1 was identified in the hexachlorocyclohexane-degrading bacterium Sphingobium indicum, and kinetic analyses demonstrate that although it is active against a wide range of antibiotics, its efficiency is lower than that of other B3 MBLs but has increased efficiency toward cephalosporins relative to other β-lactam substrates. The overall fold of SIE-1 is characteristic of the MBLs; the notable variation is observed in the Zn1 site due to the replacement of the canonical His116 by a glutamate. The unusual preference of SIE-1 for cephalosporins and its occurrence in a widespread environmental organism suggest the scope for increased MBL-mediated β-lactam resistance. Thus, it is relevant to include SIE-1 in MBL inhibitor design studies to widen the therapeutic scope of much needed antiresistance drugs.